Coalition politics and governability in post-reform Indonesia: A comparative analysis of legislative-executive relations - Zarni Adia Purna (Tamalanrea: Journal of Government and Development (JGD), 2025)
This study examines the relationship between coalition politics and governability through a comparative analysis of legislative-executive relationship dynamics in post-reform Indonesia (1999–2024). Adopting a mixed methods approach that integrates secondary statistical analysis, document analysis, and process tracing across six government periods, this study tests the proposition that coalition configuration directly determines governmental capacity. Findings demonstrate that coalition size does not correlate linearly with governability; the most determinant variable is the quality of legislative-executive coordination mechanisms, particularly hybrid mechanisms that combine institutionalized formal forums with informal coordination channels. This study also identifies a normative paradox whereby high procedural governability potentially sacrifices the quality of democratic deliberation when coalitions achieve excessive dominance. Theoretically, these findings extend the veto player theory framework and coalition governance by demonstrating that in Southeast Asian presidentialism, the institutionalization of coordination mechanisms not merely seat arithmetic constitutes the primary prerequisite for sustainable governability.